Comparative study of ultrasonography-guided percutaneous A1 pulley release versus blinded percutaneous A1 pulley release. (31st May 2018) - Lee, Sung Hyun; Choi, Young Chae; Kang, Hong Je
Purpose: The purpose of this study was to compare the results of blind versus ultrasonography-guided percutaneous A1 pulley release for treatment of trigger finger. Methods: This prospective study included 21 patients (25 fingers) who underwent blind release and 20 patients (23 fingers) who underwent ultrasonography-guided release. The visual analog scale (VAS) score, proximal interphalangeal joint contracture, complications, and patient satisfaction were compared between the groups. Results: At the final follow-up, triggering had disappeared in all patients who underwent ultrasonography-guided release, whereas three patients who underwent blind release required revision surgery for postoperative triggering. No complications were observed. VAS score was significantly different between groups at 2 and 4 weeks postoperatively. All patients who underwent ultrasonography-guided release were satisfied, whereas three patients who underwent blind release were not satisfied. Conclusion: Ultrasonography-guided percutaneous A1 pulley release for treatment of trigger finger reduces postoperative pain and complications, such as incomplete release, compared with a blind procedure.